Ownership structure and top executive turnover - Denis, David J.; Denis, Diane K.; Sarin, Atulya (Journal of Financial Economics, 1997)
We report that ownership structure significantly affects the likelihood of a change in top executive. Controlling for stock price performance, the probability of top executive turnover is negatively related to the ownership stake of officers and directors and positively related to the presence of an outside blockholder. In addition, the likehood of a change in top executive is significantly less sensitive to stock price performance in firms with higher managerial ownership. Finally, we document an unusually high rate of corporate control activity in the twelve months preceding top executive turnover. We conclude that ownership structure has an important influence on internal monitoring efforts and that this influence stems in part from the effect of ownership structure on external control threats.